Factors of social tension in the provinces of the Russian Empire in the late 19th and early 20th centuries. - Popov, Vladimir; Konchakov, Roman; Didenko, Dmitry (Cambridge Journal of Economics, 2026)
The key question of the economic and social post-reform history of Russia (after the agrarian reform of 1861) is what exactly led to the revolutions of the early 20th century. Were these revolutions a natural result of the growth of social tensions due to the flawed 'Prussian path' of the development of capitalism in agriculture (a combination of large landlords' estates and small land ownership of the bulk of the peasants) or did Russian capitalism develop successfully on the whole, and the revolutions were by no means inevitable, but rather caused by random, transient factors (war, political mistakes of the authorities and the opposition, etc.)— a brief overview of these discussions is in Nefedov and Ellman (2016). This paper aims to contribute to this discussion by analysing the patterns and causes of social protest (peasants' unrests, strikes at industrial enterprises, crimes against persons). We compute the index of inequality of land distribution for the Russian provinces, and find that the greatest increase of social protest before the First Russian Revolution of 1905–7, from the 1890s to the early 1900s, occurred in provinces with the most uneven land distribution. We speculate that this could have constituted one of the unique features of Russian development—it was the only state that experienced such a rapid territorial expansion in the era of serfdom with the result of developing extremely high land distribution inequalities in the new provinces, higher than in other European countries at the same time.